Role of steroid sulfatase in steroid homeostasis and characterization of the sulfated steroid pathway: Evidence from steroid sulfatase deficiency. (5th December 2016) - Sánchez-Guijo, Alberto; Neunzig, Jens; Gerber, Adrian; Oji, Vinzenz; Hartmann, Michaela F.; Schuppe, Hans-Christian; Traupe, Heiko; Bernhardt, Rita; Wudy, Stefan A.
Abstract: The impact of steroid sulfatase (STS) activity in the circulating levels of both sulfated and unconjugated steroids is only partially known. In addition, the sulfated steroid pathway, a parallel pathway to the one for unconjugated steroids, which uses the same enzymes, has never been characterized in detail before. Patients with steroid sulfatase deficiency (STSD) are unable to enzymatically convert sulfated steroids into their unconjugated forms, and are a good model to elucidate how STS affects steroid biosynthesis and to study the metabolism of sulfated steroids. We quantified unconjugated and sulfated steroids in STSD serum, and compared these results with data obtained from serum of healthy controls. Most sulfated steroids were increased in STSD. However, androstenediol-3-sulfate and epiandrosterone sulfate showed similar levels in both groups, and the concentrations of androsterone sulfate were notably lower. Hydroxylated forms of DHEAS and of pregnenolone sulfate were found to be increased in STSD, suggesting a mechanism to improve the excretion of sulfated steroids. STSD testosterone concentrations were normal, but cholesterol and DHEA were significantly decreased. Additionally, serum bile acids were three-fold higher in STSD. Correlations between concentrations of steroids in each group indicate that 17α-hydroxy-pregnenolone-3-sulfate in men is mainly biosynthesized from the precursor pregnenolone sulfate and androstenediol-3-sulfate from DHEAS. These findings confirm the coexistence of two steroidogenic pathways: one for unconjugated steroids and another one for sulfated steroids. Each pathway is responsible for the synthesis of specific steroids. The equal levels of testosterone, and the reduced level of unconjugated precursors in STSD, support that testosterone is primarily synthesized from sulfated steroids. In consequence, testosterone synthesis in STSD relies on an enzyme with sulfatase activity other than STS. This study reveals that STS is a key player of steroid biosynthesis regulating the availability of circulating cholesterol. Graphical abstract: Highlights: Characterization of the sulfated steroid pathway in men. Steroid sulfatase affects the biosynthesis of hormonal steroids and bile acids. Blood concentration of cholesterol sulfate increases with age.